Produksi Xilanase dari Isolat Sumber Air Panas Sonai, Sulawesi Tenggara, menggunakan Limbah Pertanian - Susilowati, Prima Endang; Raharjo, Sapto; Kurniawati, Desi; Rahim, Rahmawati; Sumarlin, Sumarlin; Ardiansyah, Ardiansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
Xylanase is the enzyme with prospec for hydrolysis hemicellulases. Many industry use xylanase thermostable. This processes require enzymes which are operationally stable at high temperature thus allowing e.g. easy mixing, better substrate solubility, high mass transfer rate, and lower risk of contamination. Thermophiles have often been proposed as sources of industrially relevant thermostable enzymes. Thermophilic bacteria, live at hot-springs, are can produced thermostable enzymes. In this work, we studied the bacteria strains isolated from water collected in the Sonai hot-springs of Southeast Sulawesi region and condition production enzyme. Screaning bacteria xylanolitic use semi-quantitative detection at agar plate with xilan, and quantitative detection activity enzyme. Result experinces in the 28 isolates screened, isolat IIA-3 (Pseudomonas sp.) showed the highest xylanase production. Organism efficiently used 2% rice straw as substrates. Pseudomonas sp. was used to hydrolyses rice straw at 50oC, agitation 150 rpm and pH 9.